HUKUM NEWTON TENTANG GERAK DALAM RUANG FASE TAK KOMUTATIF - Joko Purwanto (Kaunia: Integration and Interconnection Islam and Science, 2014)
In this paper, the Newton’s law of motions in a noncomutative phase space has been investigated. Its show that correction to the Newton’s first and second law appear if we assume that the phase space has symplectic structure consistent with the rules of comutation of the noncomutative quantum mechanics. In the free particle and harmonic oscillator case the equations of motion are derived on basis of the modified Newton’s second law in a noncomutative phase space.